2010
DOI: 10.4103/0972-5229.68218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multimodality chest physiotherapy in prevention of ventilator-associated pneumonia: A randomized clinical trial

Abstract: Background:Despite remarkable progress that has been achieved in the recent years in the diagnosis, prevention, and therapy for ventilator-associated pneumonia (VAP), this disease continues to create complication during the course of treatment in a significant proportion of patients while receiving mechanical ventilation.Objective:This study was designed to evaluate the effect of multimodality chest physiotherapy in intubated and mechanically ventilated patients undergoing treatment in the intensive care units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 24 publications
(26 reference statements)
3
39
0
5
Order By: Relevance
“…A recent study of patients undergoing pulmonary resection through open thoracotomy failed to demonstrate that preoperative chest physical therapy decreased PPCs (81); in another study, chest physical therapy for critically ill ventilated patients actually was associated with prolonged ventilation (82). Other studies, however, have shown a clear benefit from chest physical therapy with respect to ventilatory dependency (83), ICU LOS (83), and mortality (84).…”
Section: General Perioperative Strategies To Prevent Ppcsmentioning
confidence: 96%
“…A recent study of patients undergoing pulmonary resection through open thoracotomy failed to demonstrate that preoperative chest physical therapy decreased PPCs (81); in another study, chest physical therapy for critically ill ventilated patients actually was associated with prolonged ventilation (82). Other studies, however, have shown a clear benefit from chest physical therapy with respect to ventilatory dependency (83), ICU LOS (83), and mortality (84).…”
Section: General Perioperative Strategies To Prevent Ppcsmentioning
confidence: 96%
“…We evaluated effect of early‐stage rehabilitation on PICS‐related outcomes used our meta‐analysis (8 studies; Brunmmel et al .,441 Burtin et al .,442 Dantas et al .,443 Denehy et al .,444 Jones et al .,445 Kayamabu et al .,446 Pattanshetty et al .,447 and Schweickert et al 231436, 448.…”
Section: Cq18: Icu‐acquired Weakness (Icu‐aw) and Post‐intensive Carementioning
confidence: 99%
“…In a randomized study Pattanshetty and Gaude evaluated the value of multimodality chest physiotherapy in the prevention of VAP [28]. Patients in the control group received twice daily chest physiotherapy by manual hyperinflation and suctioning, while patients in the experimental group received additional chest wall vibrations and patient positioning.…”
Section: Multimodality Chest Physiotherapymentioning
confidence: 99%